2006
DOI: 10.1007/s10532-005-9024-8
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation kinetics of 2,4,6-Trichlorophenol by an acclimated mixed microbial culture under aerobic conditions

Abstract: The objective of this study was to achieve a better quantitative understanding of the kinetics of 2,4,6-trichlorophenol (TCP) biodegradation by an acclimated mixed microbial culture. An aerobic mixed microbial culture, obtained from the aeration basin of the wastewater treatment plant, was acclimated in shake flasks utilizing various combinations of 2,4,6-TCP (25-100 mg l(-1)), phenol (300 mg l(-1)) and glycerol (2.5 mg l(-1)) as substrates. Complete primary TCP degradation and a corresponding stoichiometric r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 36 publications
(45 reference statements)
2
12
0
Order By: Relevance
“…A number of studies were reported in literature on biodegradation of TCP (Armenante et al, 1999;Atuanya et al, 2000;Buitron et al, 1998;Correa et al, 2003;Vallecillo et al, 1999;Wang et al, 2000b;Garibay-Orijel et al, 2006;Snyder et al, 2006;Zilouei et al, 2006) which has an IC 50 value of 40 mg L À1 according to our determinations. Literature studies on aerobic biological treatment of TCP containing wastewaters were performed with low TCP concentrations (<150 mg L À1 ).…”
Section: Introductionsupporting
confidence: 52%
“…A number of studies were reported in literature on biodegradation of TCP (Armenante et al, 1999;Atuanya et al, 2000;Buitron et al, 1998;Correa et al, 2003;Vallecillo et al, 1999;Wang et al, 2000b;Garibay-Orijel et al, 2006;Snyder et al, 2006;Zilouei et al, 2006) which has an IC 50 value of 40 mg L À1 according to our determinations. Literature studies on aerobic biological treatment of TCP containing wastewaters were performed with low TCP concentrations (<150 mg L À1 ).…”
Section: Introductionsupporting
confidence: 52%
“…A similar pathway has been reported by Louie et al (2002) with a single difference in the formation of 2,6-dichlor-p-hydroxyquinone instead of 3,5-dichlorcatechol. 3,5-Dichlorocatechol was also detected as an intermediate in the biodegradation of TCP by Snyder et al (2006).…”
Section: Gas Chromatographic-mass Spectrometric Studiesmentioning
confidence: 92%
“…These may be the products of dehalogenation after ring cleavage (chlorocatechols) and dehalogenation before ring cleavage (2,4 or 2,6-dichlorophenol, 2-chlorophenol, catechol etc.) (Snyder et al, 2006). Mostly chlorinated aromatics degraded via ortho-cleavage, however, in some cases, successful degradation of chloroaromatics via 3-chlorocatechol using the meta-cleavage has also been reported (Farrell and Quilty, 1999).…”
Section: Gas Chromatographic-mass Spectrometric Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few reports are available which dealt with sludge samples (Sanchez et al, 2004;Smith and Novak, 1987). Snyder et al (2006) reported complete removal of 2,4,6-TCP (100 mg L 1 (0.5 mM) by aerobic mixed microbial culture obtained from the aeration basin of a wastewater treatment plant. The consortia of the bacterial isolates used in this study were able to degrade 2,4,6-TCP completely from the sludge sample when the concentration of 2,4,6-TCP was more than 100 mg L 1 (0.5 mM).…”
Section: Removal Of 246 -Tcp In Sludgementioning
confidence: 99%